2005
DOI: 10.1111/j.1439-0388.2005.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses in residual feed intake in lines of Large White pigs selected for growth rate on restricted feeding (measured on ad libitum individual feeding)

Abstract: Residual feed intake (RFI) represents the deviation of the actual ad libitum food consumption of each animal from that predicted from combination of growth rate, backfat and metabolic body weight measurements. After 4 years of divergent selection of pigs in lines for either high or low postweaning growth rate on restricted feeding, the high line exhibited a significant reduction in RFI relative to the low line. This indicated, to some extents, a lower energy requirement for maintenance in the high than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 22 publications
11
45
0
Order By: Relevance
“…Johnson et al (1999) also estimated strong genetic correlations for BF with measures of RFI not adjusted for BF (0.67 for RFI1 and RFI2). Similar results were reported by Nguyen et al (2005), who noted that selection for low RFI would improve carcass leanness in Large White pigs. Negative genetic correlations were found between LEA and all measures of RFI, which are in agreement with the estimates reported by Johnson et al (1999), who also found negative genetic correlations between LEA and four measures of RFI (ranged from −0.31 to −0.51).…”
Section: Discussionsupporting
confidence: 91%
“…Johnson et al (1999) also estimated strong genetic correlations for BF with measures of RFI not adjusted for BF (0.67 for RFI1 and RFI2). Similar results were reported by Nguyen et al (2005), who noted that selection for low RFI would improve carcass leanness in Large White pigs. Negative genetic correlations were found between LEA and all measures of RFI, which are in agreement with the estimates reported by Johnson et al (1999), who also found negative genetic correlations between LEA and four measures of RFI (ranged from −0.31 to −0.51).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, lean meat content was increased in the RFI − compared with RFI + line pigs as previously reported at an earlier stage of the selection experiment . A decrease in back-fat and an increased LMC without any change in ADG have also been reported in other selection experiments for low RFI in growing pigs (Cai et al, 2008;Johnson, Chewning, & Nugent, 1999;Mrode & Kennedy, 1993;Nguyen, McPhee, & Wade, 2005).…”
Section: Partitioning Adaptation Between Lean and Fat Tissues To Imprmentioning
confidence: 64%
“…RFI is a moderately heritable trait (Arthur et al, 2001;Nguyen et al, 2005;Hoque et al, 2009) that can be calculated as the difference in observed feed intake and expected feed intake given an animal's growth requirement for production and maintenance of body weight . It is an animal's residual from the regression line where observed equals expected that is its RFI index ( Figure 1).…”
Section: Expected Feed Intakementioning
confidence: 99%
“…Animals with a low RFI (LRFI) indexes consume less feed and are generally more efficient than high RFI (HRFI) animals. RFI is a moderately heritable trait (Arthur et al, 2001;Nguyen et al, 2005;Hoque et al, 2009), that can be used as a genetic selection tool. The Institut National de la Recherche Agronomique (INRA) and Iowa State University (ISU), have established multi-generational RFI swine selection projects.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%
See 1 more Smart Citation